Dynamic decision making under ambiguity: An experimental investigation - Georgalos, Konstantinos (Games and economic behavior, 2021)
Neoclassical economic theory assumes that whenever agents tackle dynamic decisions under ambiguity, preferences are represented by the Subjective Expected Utility (SEU) model and prior beliefs are updated according to Bayes rule, upon the arrival of partial information. Nevertheless, when one considers non-neutral ambiguity attitudes, either the axiom of dynamic consistency or of consequentialism should be relaxed. Using data from an economic experiment on dynamic choice under ambiguity, we study which of the two rationality axioms people violate, along with the question of whether this violation is part of a conscious planning strategy or not. The combination of the two, allows us to classify non-SEU subjects to three behavioural types: resolute, naïve and sophisticated. The hypothesis of Bayesian updating is rejected for more than half of the experimental population. For ambiguity non-neutral subjects, we find that the majority are sophisticated, a few are naïve and very few are resolute.